2015
DOI: 10.1103/physrevb.91.115143
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties ofTi4O7predicted by self-interaction-corrected density functional theory

Abstract: Understanding electronic properties of sub-stoichiometric phases of titanium oxide such as Magnéli phase Ti 4 O 7 is crucial in designing and modeling resistive switching devices. Here we present our study on Magnéli phase Ti 4 O 7 together with rutile TiO 2 and Ti 2 O 3 using density functional theory methods with atomic-orbital-based self-interaction correction (ASIC). We predict a new antiferromagnetic ground state in the low temperature phase (or LT phase), and we explain energy difference with a competing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
3
23
0
1
Order By: Relevance
“…1b), the present phase was only anatase with characteristic planes (101), (004), (200), (105), (211) [29], which is a new finding in this work at this temperature. The intensity of peaks corresponding to anatase increased at this temperature indicating improved crystallization of anatase phase.…”
Section: Resultssupporting
confidence: 56%
“…1b), the present phase was only anatase with characteristic planes (101), (004), (200), (105), (211) [29], which is a new finding in this work at this temperature. The intensity of peaks corresponding to anatase increased at this temperature indicating improved crystallization of anatase phase.…”
Section: Resultssupporting
confidence: 56%
“…Using LDA+U, LDA+SIC, or the HSE06 hybrid functional, the AF states are stable but the difference in energy is only 4 -5 meV per formula unit. In previous studies using LDA+U, 12 Table 2 shows the results of our DMC calculations of the energies of the FM, AF1, and AF3 states, as well as the energies from LDA+U, LDA+SIC 28 using α = 0.5, and also from HSE06 hybrid functional; 28 Table 3 shows the energy gaps obtained from LDA+U, LDA+SIC calculations (α = 0.5), and HSE06 hybrid functional. We note that neither the U-parameter in LDA+U or the α-parameter in LDA+SIC in our calculations was adjusted to fit the energy gaps.…”
Section: Resultsmentioning
confidence: 99%
“…Leonov et al 12 performed an LDA+U calculation on the low temperature phase of Ti 4 O 7 and found an energy gap in good agreement with experiment and an antiferromagnetic (AF) charge-ordered ground state; Eyert et al 25 performed LDA band structure calculation on the same low temperature structure but were unable to reproduce the spin-singlet ground state. More recently, Liborio et al 26 In a more recent study, X. Zhong et al 28 suggested two energetically competing low-energy anti-ferromagnetic states at low temperature using an atomic self-interaction correction (SIC) scheme within DFT implemented in the SIESTA 29 electronic structure code, as well as more expensive hybrid functional (HSE06) 30,31 all-electron calculations. One state was the previously studied AF state by Liborio et al, 26 while the other one was a new AF state with lower energy.…”
Section: Introductionmentioning
confidence: 99%
“…GGA+U and other advanced DFT methods such as hybrid functionals and Self-Interaction Corrections (SIC) systematically alleviate the problems of underestimating semiconductor band gaps [19][20][21][22]. We use norm-conserving pseudopotentials [23] and a plane wave cut-off at 400 Ry; a 2×2×1 k-point sampling is used for geometry relaxation and transport calculations.…”
Section: Methodsmentioning
confidence: 99%